Functional dysconnectivity of the limbic loop of frontostriatal circuits in first‐episode, treatment‐naive schizophrenia - Lin, Pan; Wang, Xiaosheng; Zhang, Bei; Kirkpatrick, Brian; Öngür, Dost; Levitt, James J.; Jovicich, Jorge; Yao, Shuqiao; Wang, Xiang (Human brain mapping, 2018)
Frontostriatal circuits dysfunction has been implicated in the etiology and psychopathology of patients with schizophrenia (SZ). However, few studies have investigated SZ‐related functional connectivity (FC) alterations in discrete frontostriatal circuits and their relationship with pathopsychology in first‐episode schizophrenia (FESZ). The goal of this study was to identify dysfunctions in discrete frontostriatal circuits that are associated with key features of FESZ. To this end, a case–control, cross‐sectional study was conducted, wherein resting‐state (RS) functional magnetic resonance (fMRI) data were collected from 37 treatment‐naïve FESZ patients and 29 healthy control (HC) subjects. Seed‐based FC analyses were performed by placing six bilateral pairs of seeds within a priori defined subdivisions of the striatum. We observed significantly decreased FC for the FESZ group relative to the HC group [ p < .05, family‐wise error (FWE)‐corrected] in the limbic loop, but not in the sensorimotor or associative loops, of frontostriatal circuitry. Moreover, bilaterally decreased inferior ventral striatum/nucleus accumbens (VSi)‐dorsal anterior cingulate cortex (dACC) FC within the limbic loop correlated inversely with overall FESZ symptom severity and the disorganization factor score of PANSS. These findings provide new insight into the role of frontostriatal limbic loop hypoconnectivity in early‐stage schizophrenia pathology and suggest potential novel therapeutic targets.